2014
DOI: 10.2495/cr140151
|View full text |Cite
|
Sign up to set email alerts
|

A tool to estimate the wheel/rail contact and temperature rising under dry, wet and oily conditions

Abstract: In this paper, finite element method (FEM) has been applied to evaluate the wheel/rail contact stress under different contact conditions. The elastic-plastic model coded in ANSYS/LS-DYNA includes a whole wheel, 680 mm of the canted rail, and sub-components of the track (railpads, sleepers, and ballast). The three values of friction coefficient 0.4, 0.2 and 0.07 have been chosen to model the dry, wet and oily environmental contacts, respectively. The high mechanical stresses exerted at the contact area will cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…For instance, the temperature in case 1 (1st axle) and case 2 (3rd axle) was 522 1C and 342 1C, respectively. This tendency was consistent with the results calculated by the analytical method in [43]. In comparison: Between AC locomotives, the temperature produced by the loco C44ACi was higher than that by the loco GT46C ACe.…”
Section: Temperature Rise On the Railsupporting
confidence: 92%
See 3 more Smart Citations
“…For instance, the temperature in case 1 (1st axle) and case 2 (3rd axle) was 522 1C and 342 1C, respectively. This tendency was consistent with the results calculated by the analytical method in [43]. In comparison: Between AC locomotives, the temperature produced by the loco C44ACi was higher than that by the loco GT46C ACe.…”
Section: Temperature Rise On the Railsupporting
confidence: 92%
“…The verification of the 3D FE model was carried out by comparing the results to the existing data from the theoretical investigations [3,43,52]. It was found that the 3D-FE temperature was lower than that obtained by the 2D-analytical temperature.…”
Section: Model Validationmentioning
confidence: 96%
See 2 more Smart Citations
“…Numerical methods have been proposed [3,4] for wheel/rail contact prediction following Kalker's work [5,6]. With the development of computing software, finite element methods (FEMs) have been more and more utilized to simulate static and dynamic wheel/rail contacts in various conditions [7,8]. However, the difficulties in simulating real surfaces with surface roughness and wear evolution put forward doubts as to whether FEM results are accurate.…”
Section: Introductionmentioning
confidence: 99%